Biocide resistance in Klebsiella pneumoniae: a narrative review - Pearl Ntshonga; Irene Gobe; Garesego Koto; Jonathan Strysko; Giacomo Maria Paganotti (Elsevier, 2024)
Summary: Klebsiella pneumoniae is among the World Health Organization's list of priority pathogens, notorious for its role in causing healthcare-associated infections and neonatal sepsis globally. Containment of K. pneumoniae transmission depends on the continued effectiveness of antimicrobials and of biocides used for topical antisepsis and surface disinfection. Klebsiella pneumoniae is known to disseminate antimicrobial resistance (AMR) through a large auxiliary genome made up of plasmids, transposons and integrons, enabling it to evade antimicrobial killing through the use of efflux systems and biofilm development. Because AMR mechanisms are also known to impart tolerance to biocides, AMR is frequently linked with biocide resistance (BR). However, despite extensive research on AMR, there is a gap in knowledge about BR and the extent to which AMR and BR mechanisms overlap remains debatable. The aim of this paper is to review and summarise the current knowledge on the determinants of BR in K. pneumoniae and highlight content areas that require further inquiry.